Bedside Rationing Under Resource Constraints—A National Survey of Ethiopian Physicians' Use of Criteria for Priority Setting. Issue 2 (3rd April 2019) - Berhane Defaye, Frehiwot; Danis, Marion; Wakim, Paul; Berhane, Yemane; Norheim, Ole Frithjof; Miljeteig, Ingrid
Abstract: In low-income settings resource constraints force clinicians to make harsh choices. We examine the criteria Ethiopian physicians use in their bedside rationing decisions through a national survey at 49 public hospitals in Ethiopia. Substantial variation in weight given to different criteria were reported by the 587 participating physicians (response rate 91.7%). Young age, primary prevention, or the patient being the family's economic provider increased likelihood of offering treatment to a patient, while small expected benefit or low chance of success diminished likelihood. More than 50% of responding physicians were indifferent to patient's position in society, unhealthy behavior, and residence, while they varied widely in weight they gave to patient's poverty, ability to work, and old age. While the majority of Ethiopian physicians reported allocation of resources that was compatible with national priorities, more contested criteria were also frequently reported. This might affect distributional justice and equity in health care access.